Coincident diabetes mellitus modulates Th1‐, Th2‐, and Th17‐cell responses in latent tuberculosis in an IL‐10‐ and TGF‐β‐dependent manner. Issue 2 (19th November 2015) - Kumar, Nathella Pavan; Moideen, Kadar; George, Parakkal Jovvian; Dolla, Chandrakumar; Kumaran, Paul; Babu, Subash
Abstract : Type 2 diabetes mellitus (DM) is a risk factor for the development of active tuberculosis (TB), although its role in the TB‐induced responses in latent TB (LTB) is not well understood. Since Th1, Th2, and Th17 responses are important in immunity to LTB, we postulated that coincident DM could alter the function of these CD4 + T‐cell subsets. To this end, we examined mycobacteria‐induced immune responses in the whole blood of individuals with LTB‐DM and compared them with responses of individuals without DM (LTB‐NDM). T‐cell responses from LTB‐DM are characterized by diminished frequencies of mono‐ and dual‐functional CD4 + Th1, Th2, and Th17 cells at baseline and following stimulation with mycobacterial antigens‐purified protein derivative, early secreted antigen‐6, and culture filtrate protein‐10. This modulation was at least partially dependent on IL‐10 and TGF‐β, since neutralization of either cytokine resulted in significantly increased frequencies of Th1 and Th2 cells but not Th17 cells in LTB‐DM but not LTB individuals. LTB‐DM is therefore characterized by diminished frequencies of Th1, Th2, and Th17 cells, indicating that DM alters the immune response in latent TB leading to a suboptimal induction of protective CD4 + T‐cell responses, thereby providing a potential mechanism for increased susceptibility to active disease.